Efektywność ochrony ubezpieczeniowej w teorii i praktyce - Handschke, Jerzy (Wydział Prawa i Administracji UAM, 1974)
Evaluation of the economic activities of the Insurance State Office (PZU) is based now in Poland on a research into effectiveness of insurance protection. By help of that method an attempt is made to measure socio-economic benefits derived from insurance institution. As the authors are not in agreement as to the idea of effectiveness of insurance protection, that way seeme unsatisfactory. The present state of things is subject to several critical remarks suggesting that evaluation of the activities of the Insurance State Office (PZU) based on an analysis of the quality of services rendered by the Office to its customers should be more accurate. The thesis is based on the conviction that research into the quality of insurance protection is easier and more accurate than research into its effectiveness, and that quality determines to a high degree effectiveness evaluated from the socio-economic point of. view. One elment of insurance protection (workability of insurance protection) deserves special attention because it is not affected by time unlike the other elements. Thus it should not be conceived in the relative sense to the changing socio-economic conditions, but exclusively in the absolute sense.